2014
DOI: 10.1016/j.bpj.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain to Main-Chain Hydrogen Bonding Controls the Intrinsic Backbone Dynamics of the Amyloid Precursor Protein Transmembrane Helix

Abstract: Many transmembrane helices contain serine and/or threonine residues whose side chains form intrahelical H-bonds with upstream carbonyl oxygens. Here, we investigated the impact of threonine side-chain/main-chain backbonding on the backbone dynamics of the amyloid precursor protein transmembrane helix. This helix consists of a N-terminal dimerization region and a C-terminal cleavage region, which is processed by γ-secretase to a series of products. Threonine mutations within this transmembrane helix are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
76
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(95 citation statements)
references
References 54 publications
19
76
0
Order By: Relevance
“…How could our present findings explain this impact of T43I? Previous MD simulations showed that the loss of the T43 side‐chain/main‐chain H‐bonding in a T43 V mutant increases the relative movements of TM−N versus TM−C at the G 37 G 38 hinge . Thereby, a very subtle local destabilization, as detected here by increasing amide exchange kinetics, can translate into profound changes of global helix dynamics.…”
Section: Figuresupporting
confidence: 51%
See 2 more Smart Citations
“…How could our present findings explain this impact of T43I? Previous MD simulations showed that the loss of the T43 side‐chain/main‐chain H‐bonding in a T43 V mutant increases the relative movements of TM−N versus TM−C at the G 37 G 38 hinge . Thereby, a very subtle local destabilization, as detected here by increasing amide exchange kinetics, can translate into profound changes of global helix dynamics.…”
Section: Figuresupporting
confidence: 51%
“…For example, the T43I (‘Austrian’) mutation (Aβ numbering) is thought to lead to an extremely early mean age‐of‐onset (36 y) by strongly increasing the Aβ42/Aβ40 ratio . The side‐chain of T43 is H‐bonded to the main chain carbonyl oxygen of V39 and controls the repertoire of TM−N versus TM−C bending motions as indicated by molecular dynamics (MD) simulations . It is unclear, however, how the loss of this H‐bond in the disease‐causing T43I mutant is connected to the flexibility of the hinge.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsic substrate TMH properties that provide conformational flexibility such as the di-glycine hinge near the middle of the APP TMH have also been shown to play an important role for cleavage 46 . Although hydrogen-deuterium exchange experiments showed that the cleavage site region in APP is generally stable with respect to local helix flexibility [46][47][48][49] , MD simulations suggested that changes in bending and rotational motions, i.e. in the global flexibility, mediated by this hinge are critical for correct presentation of the cleavage site domain to the active site 46 .…”
Section: Discussionmentioning
confidence: 99%
“…47). Threonine residues in α-helices, in particular in hydrophobic environments, often induce helical kinks, which could facilitate the repositioning of the finger helix (Cao and Bowie, 2012;Scharnagl et al, 2014).…”
Section: Figure 44mentioning
confidence: 99%